Analysis of Service, Trust, Security Impact on Satisfaction and Behavior in Shopee - Ahmad Jidan Abrar; Alfin Nurfadhilah Ramli; Dr. Osly Usman, M.Bus Syst (Journal of Digital Business and Global Economy, 2025)
The purpose of this study is to look into how security, trust, and service quality affect customer behavior on the Shopee e-commerce platform. E-commerce has grown significantly in the last several years, making the market more competitive. In this regard, it is critical for online retailers such as Shopee to comprehend the elements that influence consumer happiness and purchase behavior. Shopee users are surveyed in order to gather data for this study. This study uses statistical methods, such as regression analysis, to examine the connections between consumer behavior and elements like security, trust, and service quality. It is anticipated that the results would give Shopee and other e-commerce companies insightful information to enhance their offerings. This research intends to assist businesses develop more effective tactics to improve customer satisfaction, create trust, and promote online shopping security by analyzing the primary determinants of consumer behavior and satisfaction on Shopee's platform. Additionally, the study's findings can be a useful guide for upcoming e-commerce and digital marketing studies. This study advances our knowledge of the variables influencing customer behavior in light of the ongoing development of digital commerce. E-commerce sites like Shopee can use these data to sustain their growth and competitiveness in a business environment that is becoming more and more dynamic.